Flexural Behaviors of Precast Reinforced Concrete -EPSfoam-Steel Deck Hybrid Panel - Mardiana Oesman (Universitas Islam Sultan Agung, 2021)
This paper presented the flexural behavior of the newly developed hybrid panel which included the comparison of the ultimate load, load-deflection behavior, and failure modes. The experimental study was carried out on precast reinforced concrete-EPSfoam-steel deck hybrid panels (CES) consist of three layers of material : concrete layer is on the top, the steel deck is located on the bottom layer, and the EPS foam layer as the core. The dimensions of CES are 300 mm x 1200 mm with thickness of concrete layer and EPS foam as variables. The concrete thick were 30 mm and 40mm. The density of EPS foam was 12 kg/m3, 20 kg/m3, and 30 kg/m3. The static flexural test of CES was conducted in accordance with the ASTM C 393-00 standard for determination of flexural strength on concrete, the load was applied at third-point loading. This test was carried out with monotonic static load, deflection control using a loading frame with capacity of 10 kN. The results show that increase the thickness of the concrete layer from 30mm to 40mm with EPSfoam density of 12 kg /m3, 20 kg/m3, and 30 kg/m3 achieved a maximum load increase of 33.51%; 46,13%; and 37.35%, respectively.